Lifetime costs of traumatic brain injury identified in the emergency department in Ontario. (3rd June 2015) - Fu, T; Jing, R; Cusimano, M
Abstract : Background: Traumatic brain injury (TBI) is a leading cause of death and disability, yet there is limited research on its economic burden. We estimated the incidence and lifetime costs of TBI identified in the Emergency Department (ED) in Ontario, Canada between April 2009 and March 2010. Methods: ED visits for TBI were identified using a population-based database that is mandatory for ambulatory care facilities in Ontario. The authors calculated unit costs for medical treatment and productivity loss, and multiplied these by incidence estimates to determine the lifetime costs of identified TBI cases. Results: In 2009, there were over 133, 000 ED visits for TBI in Ontario, resulting in a conservative estimate of 945 million in total lifetime costs. Costs were greater for males than females across nearly all age groups, with males incurring two-fold higher costs overall. Together, falls (407 million), struck by/against (309 million), and motor vehicle injuries (161 million) represented 93% of lifetime costs associated with TBI. Conclusions: This study revealed a high incidence and economic burden associated with TBI identified in the ED. More research is needed to fully appreciate the burden of TBI across a variety of healthcare settings.